Nazmoun ka majmowa dhanak class 2 - Shah, Bano Alvi; Asiya, Saeed (Ushba Publishing Karachi, 2011)
"Nazmoun ka Majmooa Dhanak Class 2" is a collection of poems designed for second-grade Urdu language learners in Pakistan. This book aims to introduce young students to the beauty and rhythm of Urdu poetry.